Immunohistochemical expression of p53, p16 and hTERT in oral squamous cell carcinoma and potentially malignant disorders - Aline Correa Abrahao; Beatriz Venturi Bonelli; Fábio Daumas Nunes; Eliane Pedra Dias; Márcia Grillo Cabral (Sociedade Brasileira de Pesquisa Odontológica, 2011)
Oral carcinogenesis is a multi-step process. One possible step is the development of potentially malignant disorders known as leukoplakia and erytroplakia. The objective of this study was to use immunohistochemistry to analyze the patterns of expression of the cell-cycle regulatory proteins p53 and p16INK4a in potentially malignant disorders (PMD) of the oral mucosa (with varying degrees of dysplasia) and in oral squamous cell carcinomas (OSCC) to correlate them with the expression of telomerase (hTERT). Fifteen PMD and 30 OSCC tissue samples were analyzed. Additionally, 5 cases of oral epithelial hyperplasia (OEH) were added to analyze clinically altered mucosa presenting as histological hyperplasia without dysplasia. p53 positivity was observed in 93.3% of PMD, in 63.3% of OSCC and in 80% of OEH. Although there was no correlation between p53 expression and the grade of dysplasia, all cases with severe dysplasia presented p53 suprabasal immunoexpression. p16INK4a expression was observed in 26.7% of PMD, in 43.3% of OSCC and in 2 cases of OEH. The p16INK4a expression in OEH, PMD and OSCC was unable to differentiate non-dysplastic from dysplastic oral epithelium. hTERT positivity was observed in all samples of OEH and PMD and in 90% of OSCC. The high hTERT immunoexpression in all three lesions indicates that telomerase is present in clinically altered oral mucosa but does not differentiate hyperplastic from dysplastic oral epithelium. In PMD of the oral mucosa, the p53 immunoexpression changes according to the degree of dysplasia by mechanisms independent of p16INK4a and hTERT.